2017
DOI: 10.3390/ijms18020288
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Monophosphate (AMP)-Activated Protein Kinase: A New Target for Nutraceutical Compounds

Abstract: Adenosine monophosphate-activated protein kinase (AMPK) is an important energy sensor which is activated by increases in adenosine monophosphate (AMP)/adenosine triphosphate (ATP) ratio and/or adenosine diphosphate (ADP)/ATP ratio, and increases different metabolic pathways such as fatty acid oxidation, glucose transport and mitochondrial biogenesis. In this sense, AMPK maintains cellular energy homeostasis by induction of catabolism and inhibition of ATP-consuming biosynthetic pathways to preserve ATP levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 102 publications
2
61
0
Order By: Relevance
“…The enhanced glucose uptake by HAEF is suggesting the beneficial effect of MD-1 supplementation in insulin resistance. Presence of phytochemicals like gallic acid [41], ellagic acid [42], berberine [43] and quercetin [44] with reported activation of AMPK pathway substantiated the observed glucose uptake by MD-1 in the absence of insulin. Reported amelioration of insulin resistance by the constituent herbs [45, 46] lends support to the HAEF mediated 2-DG uptake in the presence of insulin.…”
Section: Discussionmentioning
confidence: 86%
“…The enhanced glucose uptake by HAEF is suggesting the beneficial effect of MD-1 supplementation in insulin resistance. Presence of phytochemicals like gallic acid [41], ellagic acid [42], berberine [43] and quercetin [44] with reported activation of AMPK pathway substantiated the observed glucose uptake by MD-1 in the absence of insulin. Reported amelioration of insulin resistance by the constituent herbs [45, 46] lends support to the HAEF mediated 2-DG uptake in the presence of insulin.…”
Section: Discussionmentioning
confidence: 86%
“…AMPK phosphorylates many proteins involved in autophagy regulation as well as proteins implicated in the control of cell cycle and apoptosis, like p21 and p53, strongly suppressing cell proliferation [ 20 ]. In the last few years AMPK has been identified as a target of several nutraceutical compounds that increase AMPK phosphorylation to modulate many cell functions [ 21 ]. To investigate whether capsaicin modulates AMPK and to examine the mechanism underpinning the cytotoxicity by capsaicin, we analyzed the activation of AMPK in HCC cells.…”
Section: Resultsmentioning
confidence: 99%
“…During preadipocyte differentiation and adipogenesis, AMPK is inactivated by lower phosphorylation levels (17,19). In addition, AMPK activation by phosphorylation can reduce the degree of obesity by inhibiting adipocyte differentiation by changing the expression and activity of the enzymes and proteins involved in lipid metabolism (16,19).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of AMKP inhibits preadipocyte differentiation and adipogenesis through increased phosphorylation of ACC, a substrate of AMPK (13,17). To investigate whether AMPK is activated by EEAY during 3T3-L1 differentiation, we analyzed the levels of phosphorylated AMPK and ACC and found that EEAY remarkably enhanced the phosphorylation of AMPK and ACC without altering the expression of their total protein expression, indicating the activation of the AMPK pathway.…”
Section: Eeay Induces the Phosphorylation Of Ampk And Accmentioning
confidence: 99%
See 1 more Smart Citation